Analysis of the Effect of Capital Adequacy Ratio and Non-Performing Loans on Return on Assets in 4 State-Owned Banks Listed on the IDX for the 2017-2021 Period - Dinna Charisma; Ari Bramasto; Elvina Nisa A S (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2022)
One indicator of banking financial performance can be seen through Return on Assets (ROA). This is because ROA is used to measure the effectiveness of a company in generating profits by utilizing its assets. Financial ratios such as Capital Adequacy Ratio (CAR) and Non Performing Loans (NPL) help industrial banking to evaluate and assess the soundness of a bank. This study aims to analyze the effect of Capital Adequacy Ratio (CAR) and Non-Performing Loan (NPL) on Return on Assets (ROA) in 4 state-owned banks listed on the Indonesia Stock Exchange for the period 2017-2021. The type of data used in this study is secondary data obtained from the annual financial statements of banks published on the Indonesia Stock Exchange for the period 2017-2021. The sampling technique in this study used purposive sampling with 3 criteria and the sample in this study amounted to 4 banks. The analytical method used is quantitative, processed using SPSS 25. The results show that partially the Capital Adequacy Ratio (CAR) variable has a significant positive effect on Return on Assets (ROA), while the Non-Performing Loan (NPL) variable has no significant effect to Return on Assets (ROA).